Сучасні завдання машинобудівних підприємств в умовах відтворення основних засобів сільськогосподарських підприємств - Кузьменко, Леонід Володимирович (НТУ "ХПІ", 2017)
Представлена характеристика функціональних сфер та структурних секторів агропромислового комплексу країни. Відмічена актуальність проблеми відтворення основних засобів сільськогосподарських підприємств, особливо для господарств сектору малих та середніх виробників. Підкреслено особливо важливу роль машинобудівних підприємств в процесі відтворення основних засобів аграрних підприємств. Сформульовані необхідні умови для успішного розвитку вторинного ринку та визначені, в найбільш загальній формі, критерії оцінки зацікавленості його учасників в цьому процесі.

Presented description of functional spheres and structural sectors of agroindustrial complex of country. Noted actuality of problem of recreation of capital assets of agricultural enterprises, especially for the sector of small and middle producers economic. Underline especially important role of machine-building enterprises in the recreation process of the fixed assets of agrarian enterprises. . It is shown that currently the main form of reproduction of fixed assets for the sector is restored using technology that has been in operation for 4-5 years, that the use of the secondary market. Formulated necessary conditions for the successful development of the secondary market - a mutually beneficial partnership participants. Defined in the most general terms, evaluation criteria of interest partners market in the process, the profitability recovery process technology, which has been in operation - for engineering companies and unit cost resources in different variants of state agricultural machines (new, renewed and and running for some time from date of purchase) - for agricultural enterprises. Emphasized that the active participation of engineering companies, given their current state in the process of reproduction of fixed assets of agricultural enterprises is crucial not only for the development of agriculture as a whole, but also to play, in fact, of the agricultural machinery.
Modern tasks of machine-building enterprises are in the conditions of recreation of the fixed assets of agricultural enterprises
Keywords: комплекс агропромисловий; ринок вторинний; agroindustrial complex; machine-building enterprises; secondary market